Analisis Pengaruh Penerapan Good Corporate Governance Terhadap Agency Cost Perusahaan Sawit Yang Terdaftar Di BEI Periode 2018-2022 - Dewi Kartika; Ferdyan Wana Saputra; Pramesti Nurul Adinda (LP2M Politeknik Jambi, 2024)
The aim of this research is to determine the effect of implementing good corporate governance on agency costs. The population is 24 companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period, and a sample of 15 that meet the criteria for use in this research. The sampling technique in the research is purposive sampling and panel data regression method. The independent variables used are the size of the board of directors, independent board of commissioners, managerial ownership and foreign ownership on agency costs. The problem formulation in this research aims to find out how significant the influence of the independent variable is on the dependent variable. This research uses secondary data obtained from the official website of the Indonesia Stock Exchange (www.idx.co.id) in the form of an annual report. The data analysis technique used in the research is multiple linear regression analysis using the SPSS version 22 program. Based on the results of tests carried out in SPSS, the results show that there is no significant influence between the size of the board of directors on agency costs, the independent board of commissioners has no significant influence. significant effect on agency costs, managerial ownership has no significant effect on agency costs and foreign ownership has no significant effect on agency costs. In the F test or simultaneous test, it is concluded that there is a significant influence between the size of the board of directors, independent board of commissioners, managerial ownership and foreign ownership on agency costs simultaneously. The r² value of 60.6% coefficient indicates that the independent variable simultaneously influences the dependent variable. Meanwhile, the remaining 39.4% is influenced by other variables outside this regression equation or variables that were not studied